THE STUDY OF PROKARYOTIC GENE EXPRESSION - Mihail Yu. Minaev (Teoriâ i Praktika Pererabotki Mâsa, 2018)
One of the methods to evaluate the level of gene expression is a real-time quantitative polymerase chain reaction (qPCR). Interest in the study of molecular mechanisms of gene expression and its evaluation in prokaryotes is due to the lack of research on this issue and a number of methodological problems. The paper presents a study of gene expression mechanism in prokaryotes evidence from Aeromonas salmonicida AS1 gyrase B and collagenase genes. As a result of the research, Random primer and oligo (dT) primer (two 3’-terminal nucleotides of the primer complementary to stop codon nucleotides of the transcribed DNA sequence) with anchor and adapter of our own design were tested, which are used in the reaction of reverse transcription. The use of oligo (dT) primer became possible only after polyadenylation of extracted RNA using special poly-A polymerase kit. It is determined that the developed protocol of reverse transcription (RT) using oligo (dT) primer and adapter with certain sequence on its 5’-terminus designed for further annealing of the reverse primer during real-time PCR along with preliminary polyadenylation of RNA excludes specific amplification of the background genomic DNA. This technique may be applied in evaluating the expression level of low-expression genes when high background genomic DNA content is found in the RNA sample, e.g. at the end of logarithmic growth of prokaryotic cells.ContributionAll authors bear responsibility for the work and presented data. All authors made an equal contribution to the work. Minaev M. Yu. developed scientific and methodological approaches to work, determined the scope of research, analyzed the data obtained, performed the narrative and corrected it in final. Makhova A.A. selected research objects, carried out RNA extraction, reverse transcription and PCR analysis, performed the narrative part. The authors were equally involved in writing the manuscript and bear the equal responsibility for plagiarism.Conflict of interestThe authors declare no conflict of interest.